HIV and Breastfeeding - Figueroa A., Rolando (2015)
Vertical transmission (TV) is the passage of infection from one generation to the next, usually from a mother to her son. It is also known as mother-child infection. Initially, studies of HIV (HIV) infection in infants it was recognized that vertical transmission in tropical communities and underprivileged is higher (25-48%) than in those most industrialized and richest (13-32 %). 1992 studies concluded that women; who they were already infected before pregnancy had an additional risk of 14% of TV attributable to breastfeeding and transmission in utero or during birth. The European Collaborative Study suggest that the risk of transmission of HIV-1 infected mother to her child is doubled if she breastfeeds him. If a mother becomes infected by HIV-1 postpartum, the risk of vertical transmission is 29%.